STRATEGI PENGURANGAN FOOD WASTE DI RUMAH SAKIT - Afrizal; Nila, Kurniasari Fuadiyah; Sarita, Rahmawati Irma (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Food waste in hospitals is a serious problem that impacts healthcare efficiency, environmental sustainability, and patient well-being. Food waste in hospitals mainly comes from plate waste, which is caused by factors such as food quality, patient diet, and suboptimal food distribution systems. This study aims to assess effective strategies in reducing food waste in hospitals through a systematic review of 12 relevant studies. The method used a systematic literature review with the PRISMA approach, identifying key themes that included determinants of food waste, intervention strategies, and implementation challenges. The results showed that a Life Cycle Assessment-based approach, improved menu design, staff education, and implementation of waste monitoring system were effective in reducing food waste. However, the main challenge lies in the low institutional awareness and lack of binding regulations. Therefore, supportive policies and cross-sector collaboration are needed to create more efficient and sustainable food waste management system in hospitals.